2014
DOI: 10.4161/15592294.2014.983361
|View full text |Cite
|
Sign up to set email alerts
|

RASSF6exhibits promoter hypermethylation in metastatic melanoma and inhibits invasion in melanoma cells

Abstract: Brain metastasis is a major contributor to cancer mortality, yet, the genetic changes underlying the development of this capacity remain poorly understood. RASSF proteins are a family of tumor suppressors that often suffer epigenetic inactivation during tumorigenesis. However, their epigenetic status in brain metastases has not been well characterized. We have examined the promoter methylation of the classical RASSF members (RASSF1A-RASSF6) in a panel of metastatic brain tumor samples. RASSF1A and RASSF2 have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…We also determined that low RASSF2 expression was associated with poor prognosis. Therefore, our results were similar to previous findings [31,32].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also determined that low RASSF2 expression was associated with poor prognosis. Therefore, our results were similar to previous findings [31,32].…”
Section: Discussionsupporting
confidence: 94%
“…Gharanei [31]. Recently, in a study performed by Mezzanotte et al, the authors reported that promoter methylation leading to reduced expression of RASSF6 may play an important role in melanoma development and may contribute to brain metastases [32]. We also determined that low RASSF2 expression was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 86%
“…We have found that RASSF1A appears to have little effect on MAPK signaling in mutant B-Raf driven cells but family member RASSF6 actually enhances the association of MST1 with B-Raf and suppresses the phosphorylation of ERK [55]. So B-Raf signaling may be under the influence of non-RASSF1A family members.…”
Section: Rassf1mentioning
confidence: 99%
“…It exhibits a distinct expression pattern compared to other RASSF family members and is epigenetically silenced in primary cancers, although to a lesser extent than RASSF1A and NORE1A [55, 110, 169]. RASSF6 binds directly to K-Ras via its RA domain and synergizes with activated K-Ras to induce apoptosis [168].…”
Section: Other Rassf Family Membersmentioning
confidence: 99%
“…A class of drugs called DNA methyltransferase inhibitors exist that inhibit promoter methylation, but they have a wide range of potential side effects, as they inhibit global DNA methylation [271]. More specific inhibitors that target single DNA methyltransferase enzymes have been developed, and I have shown that one of these, Nanaomycin A, can efficiently promote the re-expression of a RASSF protein in melanoma cells [125]. Thus, using therapies that specifically target NORE1A…”
Section: -Conclusionmentioning
confidence: 99%